Custom and reason in Hume a Kantian reading of the first book of the Treatise - Allison, Henry E. (Oxford : Oxford University Press, 2008)
Henry Allison offers a new understanding of Hume's theory of knowledge, as contained in the first book of his Treatise. Allison provides a comprehensive and detailed critical analysis of Hume's views on the subject, and an extensive comparison with Kant on a range of issues including space and time.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hume, David, -- 1711-1776.; Kant, Immanuel, -- 1724-1804.; Knowledge, Theory of